TRPV4-mediated regulation of the blood brain barrier is abolished during inflammation - Rosenkranz, Sina Cathérine; Tsvilovskyy, Volodymyr; Freichel, Marc (Frontiers in cell and developmental biology, 2020)
Blood-brain barrier (BBB) dysfunction is critically involved in determining the extent of several central nervous systems (CNS) pathologies and here in particular neuroinflammatory conditions. Inhibiting BBB breakdown could reduce the level of vasogenic edema and the number of immune cells invading the CNS, thereby counteracting neuronal injury. Transient receptor potential (TRP) channels have an important role as environmental sensors and constitute attractive therapeutic targets that are involved in calcium homeostasis during pathologies of the CNS. TRPV4 is a calcium permeable, nonselective cation channel highly expressed in endothelial cells. As it is involved in the regulation of the blood brain barrier permeability and consequently cerebral edema formation, we anticipated a regulatory role of TRPV4 in CNS inflammation and subsequent neuronal damage. Here, we detected an increase in transendothelial resistance in mouse brain microvascular endothelial cells (MbMECs) after treatment with a selective TRPV4 inhibitor. However, this effect was abolished after the addition of IFNγ and TNF indicating that inflammatory conditions override TRPV4-mediated permeability. Accordingly, we did not observe a protection of Trpv4-deficient mice when compared to wildtype controls in a preclinical model of multiple sclerosis, experimental autoimmune encephalomyelitis (EAE), and no differences in infarct sizes following transient middle cerebral artery occlusion (tMCAO), the experimental stroke model, which leads to an acute postischemic inflammatory response. Furthermore, Evans Blue injections did not show differences in alterations of the blood brain barrier (BBB) permeability between genotypes in both animal models. Together, TRPV4 does not regulate brain microvascular endothelial permeability under inflammation.
Gesehen am 07.12.2020